233k views
5 votes
PLEASE HELP ASAP!!! CORRECT ANSWER ONLY PLEASE!!!

Simplify.

Assume x and z are nonnegative.

PLEASE HELP ASAP!!! CORRECT ANSWER ONLY PLEASE!!! Simplify. Assume x and z are nonnegative-example-1
User Richeek
by
5.1k points

2 Answers

5 votes


3√(32x^4z)=3√(32)\cdot√(x^4)\cdot√(z)\\\\=3√(16\cdot2)\cdot√((x^2)^2)\cdot√(z)\\\\=3√(16)\cdot\sqrt2\cdot x^2\cdot√(z)\\\\\=3\cdot4\cdot\sqrt2\cdot x^2\cdot√(z)\\\\=12x^2√(2z)\\\\Used:\\\\√(a\cdot b)=√(a)\cdot√(b)\\\\√(a^2)=a

User Alan Ivey
by
5.3k points
4 votes
3√32x^4z

= 3√(2^5)* x^4 *z

(Square rooting the terms)

= 3*2*2*x*x√2*z

=12x^2√2z

User Forhad Ahmed
by
5.8k points